2011
DOI: 10.1177/0883073811409227
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Valproic Acid and Carbamazepine Treatment on Serum Biotin and Zinc Levels and on Biotinidase Activity

Abstract: We determined the serum concentration of biotin, zinc, antiepileptic drugs, and biotinidase enzyme activity in 20 children treated with valproic acid, in 10 children treated with carbamazepine, and in 75 age- and sex-matched healthy controls. There were no significant differences in the serum levels of biotin, and biotinidase enzyme activity between the patients treated with valproic acid, the patients treated with carbamazepine, and the control group. Zinc serum levels were lower in the patients treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Hair regrowth in this patient occurred after 2 months of biotin supplementation. Only 1 study conducted by Castro-Gago et al [14] showed decreased levels of both biotin and biotinidase secondary to medication usage (valproic acid) that improved after 3 months of supplementation with biotin. Finally, 3 cases of brittle nail syndrome treated with biotin were found in the literature and each case showed improvement of nail strength as well as growth on either 2,500 or 3,000 μg of biotin/day.…”
Section: Methodsmentioning
confidence: 99%
“…Hair regrowth in this patient occurred after 2 months of biotin supplementation. Only 1 study conducted by Castro-Gago et al [14] showed decreased levels of both biotin and biotinidase secondary to medication usage (valproic acid) that improved after 3 months of supplementation with biotin. Finally, 3 cases of brittle nail syndrome treated with biotin were found in the literature and each case showed improvement of nail strength as well as growth on either 2,500 or 3,000 μg of biotin/day.…”
Section: Methodsmentioning
confidence: 99%
“…Prophylactic use of antiepileptic drugs has been considered to reduce the recurrence of complex FS [4], but it can also induce several side effects, such as drowsiness, hyperactivity, or learning difficulties by phenobarbital [5] and weight gain, nausea, hair loss, or liver injury by valproic acid [6], [17][19]. The development of less toxic prophylactic treatments for complex FS is thus necessary to help children with FS, and we therefore analyzed the effect of a herbal medicine that has been widely used in Asian countries.…”
Section: Discussionmentioning
confidence: 99%
“…Davison et al 2011 It may reduce the serum and hair zinc. Armutcu et al 2004Yilmaz et al 2009Castro-Gago et al 2011 High-fat diet and soy intake with drug should be avoided. Zhang et al 2014Marahatta et al 2014 Gabapentin, pregabalin, carbamazepine and VPA High protein intake may prevent levodopa to cross blood brain barrier.…”
Section: Anticonvulsant/antiepileptic Drugsmentioning
confidence: 99%